2016
DOI: 10.1038/srep37611
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into the oxidation reactivity and nanostructure of particulate matter from diesel engine fuelled with diesel/polyoxymethylene dimethyl ethers blends

Abstract: This paper focuses on oxidation reactivity and nanostructural characteristics of particulate matter (PM) emitted from diesel engine fuelled with different volume proportions of diesel/polyoxymethylene dimethyl ethers (PODEn) blends (P0, P10 and P20). PM was collected using a metal filter from the exhaust manifold. The collected PM samples were characterized using thermogravimetric analysis (TGA), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Raman spectroscopy. The TGA results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
1
24
0
1
Order By: Relevance
“…The oxygen content in bio-alcohols fuels can reduce the soot formation rate and enhance the formed particles oxidation rates during the combustion process, [21]. These results are similar than the found for diesel bio-alcohol fuels combustion as reported in literature [48,49], where in these cases, bio-alcohols even showed slightly lower primary particles diameters due to the oxygen content.…”
Section: Primary Particle Diameter (D P0 ) Analysissupporting
confidence: 86%
“…The oxygen content in bio-alcohols fuels can reduce the soot formation rate and enhance the formed particles oxidation rates during the combustion process, [21]. These results are similar than the found for diesel bio-alcohol fuels combustion as reported in literature [48,49], where in these cases, bio-alcohols even showed slightly lower primary particles diameters due to the oxygen content.…”
Section: Primary Particle Diameter (D P0 ) Analysissupporting
confidence: 86%
“…The higher magnification image showed that this surface is rather lumpy, consisting of many minute particles (of 30-70 nm dimension) combining in larger agglomerates. Moreover, as noted by Yang et al (2016), the nanostructure of particulate matter is highly dependent on the fuel oxygen content [17].…”
Section: Nanoparticles' Morphologymentioning
confidence: 88%
“…It was demonstrated that non-pollution-derived particles with a more defined, sharper edge displaced lung surfactant to a larger degree than those with a spherical composition, allowing these particles to be more readily internalised by the lung epithelium (Gerber et al 2006 ). To date, combustion-derived PM is reported to consist of aggregates of carbonaceous spherules with a smooth appearing surface (Yang et al 2016 , Zeb et al 2018 ). Recently, a novel method was developed to visually assess volcanic PM in 3D by high-resolution laser scanning confocal microscopy (Wertheim et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%